THE EFFECT OF SMOKING ON RESPONSE TO TUMOR NECROSIS FACTOR-ALPHA INHIBITOR TREATMENT IN ANKYLOSING SPONDYLITIS PATIENTS: RESULTS FROM THE TURKBIO REGISTRY - Tugsal, H. Yarkan; Can, G.; Capar, S.; Zengin, B.; Kenar, G.; Akar, S.; Onen, F. (Bmj Publishing Group, 2018)
[Abstract Not Available]
Congress of the European-League-Against-Rheumatism (EULAR) -- JUN 13-16, 2018 -- Amsterdam, NETHERLANDS